Evaluation of Ocean Biogeochemistry and Carbon Cycling in CMIP Earth System Models With the International Ocean Model Benchmarking (IOMB) Software System. Issue 10 (2nd October 2022) - Fu, Weiwei; Moore, J. Keith; Primeau, Francois; Collier, Nathan; Ogunro, Oluwaseun O.; Hoffman, Forrest M.; Randerson, James T.
Abstract: The International Ocean Model Benchmarking (IOMB) software package is a new community resource that we use here to evaluate surface and upper ocean biogeochemical variables and integrated anthropogenic carbon uptake from earth system models (ESMs) contributing to the 5th and 6th phases of the Coupled Model Intercomparison Project (CMIP5 and CMIP6). IOMB generates graphics and tables for systematically comparing model predictions against multiple datasets. Our analysis reveals some improvement in the multi‐model mean from CMIP5 to CMIP6 for most of the variables we examined. Compared to data‐constrained estimates of ocean anthropogenic carbon uptake for the 1994–2007 period, negative biases exist for many models between 30 and 50°S. Global model estimates of anthropogenic carbon uptake for the same period do not change significantly from CMIP5 to CMIP6, with the combined ensemble mean estimate of 27.8 ± 0.5 Pg C lower than a data‐constrained estimate of 33.0 ± 4.0 Pg C. At the same time, the change in the natural carbon inventory from CMIP is estimated to be a source of 0.7 ± 0.3 Pg C, which is considerably smaller in magnitude than a data‐constrained estimate of 5.0 ± 3.0 Pg C. With chlorofluorocarbon (CFC) predictions available for several models, we demonstrate that negative anthropogenic dissolved inorganic carbon biases coincide with negative biases in CFC concentration, highlighting the importance of weak exchange between the surface and interior ocean in regulating rates of anthropogenic carbon uptake. To examine the robustness of this attribution across the CMIP models, we calculate the global vertical temperature gradient between 200 and 1, 000 m as a metric for global stratification and exchange between the surface and deeper waters. We find a linear relationship between the bias of the vertical temperature gradients and the bias in global anthropogenic carbon uptake, consistent with the hypothesis that model biases in anthropogenic carbon uptake are related to biases in surface‐to‐interior exchange by physical processes. Plain Language Summary: With increasing complexity of earth system models and a rapidly expanding set of ocean observations, we develop an International Ocean Model Benchmarking system, which quantitatively assesses model performance and provides different ways to visualize model‐data differences. Our analysis reveals general improvement in the newer generation of ocean biogeochemistry models used to support the 6th Intergovernmental Panel on Climate Change (IPCC) Assessment, compared to an earlier generation of models used to support the 5th IPCC Assessment. A common feature of both generations of ocean models is on average, they absorb less human‐emitted carbon dioxide from the atmosphere during a period when observations are available between 1994 and 2007. Comparison of chlorofluorocarbon simulations reported by a few of the models with observations indicates that ocean transport and mixing may be responsible for some of the error in anthropogenic carbon. Comparison with the global temperature profile suggests that in some models, carbon dioxide absorbed at the surface is not pumped into the deeper ocean at a fast‐enough rate by circulation and mixing. Key Points: The International Ocean Model Benchmarking tool is used to evaluate the performance of Coupled Model Intercomparison Project (CMIP)‐class earth system models for upper ocean physical and biogeochemical variables Model performance improves overall from CMIP5 to CMIP6, particularly for surface nutrients, surface salinity, and mixed layer depth A low bias in model anthropogenic carbon uptake from 1994 to 2007 is related to the vertical temperature gradient between 200 and 1, 000 m